MAKTABGACHA VA BOSHLANG’ICH TA’LIMINING UZVIYLIGINI PSIXOLOGIK-PEDAGOGIK QO’LLAB-QUVVATLASH - Tleumbetova, K.; Shamuratova, X. (SCIENCE and SOCIETY, 2020)
The article discusses the problem of psychological support for the continuity of preschool and primary education in the continuons education system. The author states about the need to achieve consistency in the content and methods of educational technologies, psychological and educational activities. The importance of the methodology of preschool education lies in the fact that they take into account not only the principles of continuity, but also the development of relevant aspects of ensuring continuity in preschool education.